Socioeconomic Differentials in Employment Status and Involvement in Household Decision-Making Among Ever-Married Women in Nigeria - Soetan, Rosemary O.; Obiyan, Mary O. (Frontiers in Sociology, 2019)
Prior studies have assessed economic/instrumental dimensions of women’s empowerment relative to its agency dimensions. This study assessed ever-married women’s participation in the labour market as an agency for empowerment, household decision-making in Nigeria. The study utilises secondary data from three national surveys of Nigeria’s 2003, 2008 and 2013 Demographic and Health Surveys (DHS) to assess the differences and relationship between indices and status of women’s labour market participation and their empowerment or household decision making over an 11-year period. Explanatory variables adopted were age group, religion, employment status, educational level, household wealth index and region. Binomial logistic regression was used to predict the proxy variables of women empowerment from the explanatory variables. Findings showed that women’s access to paid employment, the educational status, and the household wealth index improved their participation in household decision-making. However, the single factor that consistently increased the likelihood of an ever-married woman to be involved in all forms of household decision- making from 2008 to 2013 was the household wealth. Also, religion affected the ability of ever-married women to participate in household decision-making. The ability of Muslim women to participate in all forms of decision-making decreased from 2008 to 2013. The study concluded that the factors that will enhance household wealth will enhance married women’s ability to be involved in household decision-making. Education of women is, however, a significant contribution to enhancing a balance of inequity between men and women in household decision-making. The attenuating effect of Islam on this prospect needs further investigation and interventions for married women living in Northern Nigeria.